PENGARUH DUKUNGAN ORANG TUA DAN KEMAMPUAN MEMBANGUN RELASI TERHADAP MOTIVASI BERWIRAUSAHA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA - Ekasari, Aldila Kurnia (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
This study aimed to analyze the effect of parental support and the ability to build relationships and simultaneous partial towards entrepreneurship motivation in students of the Faculty of Economics at the State University of Surabaya. The sample is accidental sampling purposive sampling that students who already have a business that is as many as 58 people. The analysis technique used is multiple regression. From the results of this study concluded that the results showed that; 1) there is a significant influence parental support partially on entrepreneurship motivation of 19.2%. 2) there was a significant effect of the ability to build relationships partially on entrepreneurship motivation of 32.5%. 3) there is a significant influence parental support and the ability to build relationships simultaneously towards entrepreneurship motivation of 92.3%